An Advanced Method for Repairing Severely Damaged Beams in Shear with Externally Bonded Steel Plates Using Adhesive and Steel Connectors - Alshaikhly A.S.; Alam M.A.; Mustapha K.N. (Springer Verlag, 2023)
Repairing and strengthening of damaged reinforced concrete (RC) beams using externally bonded (EB) steel plates has gained universal acceptance. The disadvantage of this method, however, is the premature debonding of the externally bonded strip, which is brittle and an undesired mode of failure. It is also known that the debonding failure of EB steel plates prevents the RC beam from reaching its full strengthening capacity. This study aims to increase the scientific understanding of the behaviour of fully damaged RC beams strengthened/retrofitted in shear by means of EB steel plates. It also concentrates on preventing or delaying premature debonding of the adhesively bonded steel plates using new embedded adhesive and steel connectors. To achieve these objectives, seven beams with a deficient shear design were loaded monotonically up to maximum load capacities and repaired using the proposed connectors. One beam was used as a reference beam; the other six damaged beams were repaired with vertical and inclined steel plates. The presence/absence of the new embedded connectors was investigated with these two types of configurations. Theoretical models were also proposed to predict the effective debonding strain and the shear capacities of beam specimens. A comparison among these beams was done to investigate the efficiency of these connectors to enhance the bond strength between the externally bonded steel plates and the concrete surface on the web sides of the repaired RC beams. It is concluded that using steel and adhesive connectors to fix EB steel plates for repairing severely shear-damaged RC beams can delay the premature debonding failure and restore the original shear capacity of the these beams. Finally, the proposed model was satisfactorily verified through the experimental investigations and with the current design guidelines. 2016, King Fahd University of Petroleum & Minerals.